In pursuit of social justice in South African higher education: Exploring the relationship between epistemological access and the development of students' academic literacies - Collett, K. S.; Dison, A.; Du Plooy, L. (South African Journal of Higher Education, 2024)
The concept of epistemological access, formulated by Morrow (1994; 2007), has been highly influential in higher education. It has been widely used in the sense of moving beyond physical or formal access to meaningful access to the “goods” of the university. An academic literacy approach acknowledges the complexity of literacy practices at university level. According to this approach, students need to master disciplinary literacies in order to learn and engage with knowledge (Lea and Street 1998; 2006). Epistemological access, social justice and academic literacies have been widely researched in the South African higher education field. This conceptual article explores the relationship between epistemological access and the development of students’ academic literacies to enhance social justice within the South African higher education context. We draw on related literature and our current experiences as academics to critique current institutional practices aimed at addressing the development of academic literacies and promoting student success. We argue for greater attention to be paid at institutional and faculty level to enhancing epistemological access and social justice. This article ends by putting forward a number of propositions towards strengthening student epistemological access and academic literacies development in higher education from a social justice perspective.